The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/and.13353
|View full text |Cite
|
Sign up to set email alerts
|

The antiapoptotic and antioxidant effects of eugenol against cisplatin‐induced testicular damage in the experimental model

Abstract: Testicular dysfunction or damage is among the critical side effects of chemotherapeutic drugs like cisplatin. This study was mapped out to assess the possible therapeutic effect of eugenol on cisplatin‐induced testicular damage. In this experimental study, a single dose of cisplatin (15 mg/kg) was given intraperitoneally. After 72 hr of cisplatin injection, rats were sacrificed and testis tissues were removed. Tissues were examined by biochemical, histopathological and immunohistochemical methods. While tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…A single dose of CISP (10 mg/kg, dissolved in 5 % DMSO/saline) was administered by intraperitoneal injection to the rats in the CISP and CISP+NRCE groups. The dose of CISP and NRCE were chosen based on previous literature [11,33] . After the last day of treatment, the rats were euthanized with sodium thiopental (150 mg/kg) and blood samples were obtained through cardiac puncture, centrifuged (3000 rpm for 15 min at 4 °C) to obtain the sera, which was subsequently used for the determination of testosterone and follicle stimulating hormone (FSH) levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single dose of CISP (10 mg/kg, dissolved in 5 % DMSO/saline) was administered by intraperitoneal injection to the rats in the CISP and CISP+NRCE groups. The dose of CISP and NRCE were chosen based on previous literature [11,33] . After the last day of treatment, the rats were euthanized with sodium thiopental (150 mg/kg) and blood samples were obtained through cardiac puncture, centrifuged (3000 rpm for 15 min at 4 °C) to obtain the sera, which was subsequently used for the determination of testosterone and follicle stimulating hormone (FSH) levels.…”
Section: Methodsmentioning
confidence: 99%
“…The dose of CISP and NRCE were chosen based on previous literature. [11,33] After the last day of treatment, the rats were euthanized with sodium thiopental (150 mg/kg) and blood samples were obtained through cardiac puncture, centrifuged (3000 rpm for 15 min at 4°C) to obtain the sera, which was subsequently used for the determination of testosterone and follicle stimulating hormone (FSH) levels. The testes were rapidly excised, rinsed with normal saline and weighed.…”
Section: Experimental Designmentioning
confidence: 99%
“…Eugenol is one of active compounds of a well-known traditional Chinese medicine Acorus gramineus, which has attracted wide attention for its antiinflammatory (El-Kady et al, 2019), antiapoptotic (Ekinci Akdemir et al, 2019), antioxidant (Ekinci Akdemir et al, 2019), and antitumor (Fangjun and Zhijia, 2018) effects. A previous study showed that eugenol could protect against hepatic ischemia-reperfusion injury (Abd El Motteleb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Testicular oxidative stress has been reported to be detrimental to male fertility health (Turner & Lysiak, 2008; Yesil et al., 2018). The use of exogenous antioxidants such as eugenol (Table 1) have been reported to improve testicular dysfunctions (Aitken & Roman, 2009; Ekinci akdemir et al., 2019; Imam et al., 2017). The ability of the infusion to restore the testicular antioxidant capacity indicates a potent protective effect against oxidative testicular injury, which may be attributed to its phenolic content.…”
Section: Discussionmentioning
confidence: 99%